Citizen science and the power of public participation in marine spatial planning. (July 2015) - Jarvis, Rebecca M.; Bollard Breen, Barbara; Krägeloh, Christian U.; Billington, D. Rex
Abstract: Marine spatial planning (MSP) is becoming increasingly used in the sustainable management of marine and coastal ecosystems. However, limitations on time and resources often restrict the data available for MSP and limit public engagement and participation in the MSP process. While citizen science is being increasingly used to provide fine-scale environmental data across large terrestrial planning areas, there has been little uptake in MSP to date. This paper demonstrates how consistent citizen observations can be used to identify hotspots of good and poor environmental health across a MSP region, and where environmental health has improved or degraded in the past five years; information that is difficult to obtain by other means. The study demonstrates how citizen science provides valuable insight into environmental health across a MSP region, while fostering a supportive space for the public to contribute their own observations and participate in the planning process. Highlights: Citizen science enhanced public participation in marine spatial planning (MSP). Provided fine-scale data across a MSP region difficult to achieve by other methods. Identified hotspots of good and poor environmental health. Identified hotspots where health had improved or degraded in the past five years. Supportive space for the public to contribute local environmental knowledge.